Plant Growth Promoting and Biocontrol Activity of Streptomyces spp. as Endophytes - Vurukonda, Sai Shiva Krishna Prasad (Int J Mol Sci, 2018)
There has been many recent studies on the use of microbial antagonists to control diseases incited by soilborne and airborne plant pathogenic bacteria and fungi, in an attempt to replace existing methods of chemical control and avoid extensive use of fungicides, which often lead to resistance in plant pathogens. In agriculture, plant growth-promoting and biocontrol microorganisms have emerged as safe alternatives to chemical pesticides. Streptomyces spp. and their metabolites may have great potential as excellent agents for controlling various fungal and bacterial phytopathogens. Streptomycetes belong to the rhizosoil microbial communities and are efficient colonizers of plant tissues, from roots to the aerial parts. They are active producers of antibiotics and volatile organic compounds, both in soil and in planta, and this feature is helpful for identifying active antagonists of plant pathogens and can be used in several cropping systems as biocontrol agents. Additionally, their ability to promote plant growth has been demonstrated in a number of crops, thus inspiring the wide application of streptomycetes as biofertilizers to increase plant productivity. The present review highlights Streptomyces spp.-mediated functional traits, such as enhancement of plant growth and biocontrol of phytopathogens.